Combining Raman and infrared spectroscopy as a powerful tool for the structural elucidation of cyclodextrin-based polymeric hydrogels. Issue 15 (21st April 2015) - Venuti, V.; Rossi, B.; D'Amico, F.; Mele, A.; Castiglione, F.; Punta, C.; Melone, L.; Crupi, V.; Majolino, D.; Trotta, F.; Gessini, A.; Masciovecchio, C.
<x xml:space="preserve">Abstract</x> UV Raman spectroscopy and infrared spectroscopy have been efficiently implemented for the structural and dynamic elucidation of cyclodextrin-based polymeric hydrogels.